Variation in Neonatal Nutrition Practice and Implications: A Survey of Australia and New Zealand Neonatal Units - McLeod, Gemma; Farrent, Shelley; Gilroy, Melissa; Page, Denise; Oliver, Colleen J.; Richmond, Fiona; Cormack, Barbara E. (Frontiers in Nutrition, 2021)
Background: Significant global variation exists in neonatal nutrition practice, including in assigned milk composition values, donor milk usage, fortification regimens, probiotic choice and in methods used to calculate and report nutrition and growth outcomes, making it difficult to synthesise data to inform evidence-based, standardised nutritional care that has potential to improve neonatal outcomes. The Australasian Neonatal Dietitians' Network (ANDiN) conducted a survey to determine the degree to which neonatal nutritional care varies across Australia and New Zealand (A&NZ) and to highlight potential implications. Materials and Methods: A two-part electronic neonatal nutritional survey was emailed to each ANDiN member (n=50). Part-One was designed to examine individual dietetic practice; Part-Two examined site-specific nutrition policies and practices. Descriptive statistics were used to examine the distribution of responses. Results: Survey response rate: 88%. Across 24 NICU sites, maximum fluid targets varied (150-180 mL.kg.d-1); macronutrient composition estimates for mothers’ own(MOM) and donor (DM) milk varied (Energy (kcal.dL-1) MOM: 65-72; DM 69-72: Protein (g.dL-1): MOM: 1.0-1.5; DM: 0.8-1.3); pasteurised DM or unpasteurised peer-to-peer DM was not available in all units; milk fortification commenced at different rates and volumes; a range of energy values (kcal.g-1) for protein (3.8-4.0), fat (9.0-10.0) and carbohydrate (3.8-4.0) were used to calculate parenteral and enteral intakes; probiotic choice differed; and at least 7 different preterm growth charts were employed to monitor growth. Discussion: Our survey identifies variation in preterm nutritional practice across A&NZ of sufficient magnitude to impact nutritional interventions and neonatal outcomes. This presents an opportunity to use the unique skillset of neonatal dietitians to standardise practice, reduce uncertainty of neonatal care and improve the quality of neonatal research.